The prediction of power and efficiency during near-maximal rowing - Jensen, R. L.; Freedson, P. S.; Hamill, J. (European Journal of Applied Physiology, 1996)
The relationship between power and gross efficiency during near-maximal rowing, and physiological measures of strength, power, aerobic and anaerobic capacities and United State Rowing Association (USRA) performance tests (independent variables) was investigated among collegiate male rowers. Criterion measures of rowing power and gross efficiency were measured in a moving-water rowing tank, using an oar instrumented with strain gauges to assess force and a potentiometer to assess oar position. Bivariate correlation analysis (n = 28) indicated no relationship between the independent variables and rowing gross efficiency (P > 0.05). Rowing power [mean (SD) 483.4 (34.75) W] was significantly related to inboard leg extension strength (IL strength, r = 0.63), outboard leg extension strength (r = 0.45), combined leg extension strength (r = 0.45), and time to complete the USRA 2000-m simulated rowing race (r = -0.52; P <0.05). Stepwise regression using resampling cross-validation of 15 random samples (21 subjects per sample selected from a total group of 28 intercollegiate oarsmen) indicated that predictors of rowing power were IL strength and blood lactate following a peak oxygen uptake rowing test with significant multiple correlations of R 0.61 to 0.86 (P <0.05). The standard error of estimate (SEM) ranged from 18.1 to 29.9 W, or 5.3 (0.77) percent of the criterion value. Cross-validation with a hold-out group (seven subjects per sample) was performed for each equation and correlations ranged from R = 0.14 to 0.97 (SEM = 8.0 to 38.9 W). In conclusion, data from the present study suggest that to increase rowing power, training should emphasize leg strength and anaerobic training to decrease the level of lactate accumulated during rowing.